Making Hidden Sustainable Urban Planning and Landscape Knowledge Visual and Multisensorial - Carlos J. L. Balsas (Land)
Many cityscapes and landscapes create reactions of awe due to their unexpected characteristics or uniqueness. First glance observations may not reveal or enable the understanding of all natural, social, economic, environmental, and cultural processes taking place at a given moment or, particularly, how those places have evolved and been transformed into being what they are today. Research helps to uncover hidden layers of reality and make sense of relationships among elements, dimensions, and processes. Distinct research styles of variable intensity and comprehensiveness are required to respond to the needs of multiple stakeholders. Quantitative research methods have become increasingly sophisticated, and while they serve to enhance one’s knowledge of complex phenomena, they can also be difficult to understand. To what extent can urban planners and landscape architects utilize visual and multisensorial literacies to bring about more transparency and significance to territorial transformation processes? This paper analyzes how four educational and research programs implemented at the University at Albany built upon visual and multisensorial research methods to augment educational outcomes, bolster scholarly significance, and provide up-to-date knowledge to empower concerned stakeholders to help change unsustainable urbanization practices, social inequities and injustices in cities, car dependence and sedentary lifestyles, protect natural resources and livelihoods, while reducing environmental and social harm. The methods comprised literature reviews, self-reflections on the implemented programs, and analyses of participant evaluations of various outreach activities. The paper concludes with remarks for other researchers interested in making their pedagogical and scholarly activities more effective and rewarding for themselves and their intended beneficiaries.